Effectiveness-implementation hybrid type 2 trial evaluating two psychoeducational programmes for severe hypoglycaemia in type 1 diabetes: implementation study protocol. Issue 11 (14th November 2019) - Soukup, Tayana; Hull, Louise; Smith, Emma Lauretta; Healey, Andy; Bakolis, Ioannis; Amiel, Stephanie A; Sevdalis, Nick; Group, PWD
Abstract : Introduction: Two of the most acute and feared complications in type 1 diabetes (T1D) are hypoglycaemia and severe hypoglycaemia (SH). While impaired awareness of hypoglycaemia (IAH) can lead to SH with cognitive and motivational barriers implicated, the available education does not integrate behavioural change techniques to address these. A novel Hypoglycaemia Awareness Restoration Programme despite optimised care (HARPdoc) is currently being tested against an established blood glucose awareness training (BGAT) within a parallel, two-arm, group randomised, blinded trial (with its own protocol; NCT02940873 ) with adults with T1D whose problems with hypoglycaemia and SH have persisted despite otherwise optimised insulin management. While both programmes are aimed at reducing hypoglycaemia, SH and IAH, it is the former that integrates behavioural change techniques. The aim of the current (implementation) study is to evaluate delivery of both HARPdoc and BGAT and explore associations between implementation outcomes and trial endpoints; as well as to develop an evidence-based implementation blueprint to guide implementation, sustainment and scale-up of the effective programmes. Methods and analysis: Guided by the implementation science tools, frameworks, methods and principles, the current study was designed through a series of focus groups (n=11) with the key intervention stakeholders (n=28)—including (1) individuals with lived experience of T1D, IAH and a pilot version of the HARPdoc (n=6) and (2) diabetes healthcare professionals (n=22). A mixed-methods approach will be used throughout. Stakeholder engagement has underpinned study design and materials to maximise relevance, feasibility and impact. Ethics and dissemination: The protocol has been reviewed and received ethical approval by the Harrow Research Ethics Committee (18/LO/1020; 240752) on 1 October 2018. The findings will be submitted to a peer-reviewed journal and presented at scientific meetings. Trial registration number: NCT02940873 ; Pre-results.